Self-decomposition Method for Power Generators' Medium- and Long-term Contract Based on Conditional Robust Profit - Qin, Han; Liu, Shuai; Jiang, Jingwen; Zhang, Shaohua (2023 IEEE International Conference on Power Science and Technology (ICPST), 2023)
Under the requirement of time linkage between contract trading and market trading, power generators' medium- and long-term contracted electricity must be decomposed to a short time scale. To address this problem, a self-decomposition model for a generator's medium- and long-term contracted energy based on conditional robust profit is proposed, taking into consideration the uncertainty of spot market prices. This model aims to maximize the generator's conditional robust profit in the spot market, and the generator's operation and contract decomposition constraints are considered. In addition, an auxiliary variable is employed to transform the model into a tractable formulation. Finally, the effectiveness of the model is verified by numerical examples. It is shown that the proposed model can accommodate the risk preferences of the generator, which means sound strategies can be formulated according to the different levels of risk aversion.